Replication of CD58 and CLEC16A as genome-wide significant risk genes for multiple sclerosis. - Hoppenbrouwers, I; Aulchenko, Y; Janssens, A; Ramagopalan, S; Broer, L; Kayser, M; Ebers, G; Oostra, B; van Duijn, C; Hintzen, R (2009)
A recent genome-wide association study by the International Multiple Sclerosis Genetics Consortium (IMSGC) reported association of 17 single-nucleotide polymorphisms (SNPs) in 14 loci with multiple sclerosis (MS). Only two loci, HLA-DRA and IL2RA, reached genome-wide significance (P<5E-08). In our study, we determined whether we could replicate the results of the IMSGC and whether more SNPs are genome-wide significantly associated with MS. We assessed the association between the 17 IMSGC SNPs and MS in three cohorts (total number of subjects 3981, among these 1853 cases). We performed a meta-analysis of the results of our study, the original IMSGC results and the results of a recent replication study performed in the Australian population. Of the 17 IMSGC SNPs, five SNPs showed genome-wide significant association with MS: HLA-DRA (P=8E-124), IL7R (P=6E-09), IL2RA (P=1E-11), CD58 (P=4E-09) and CLEC16A (P=3E-12). Therefore, genome-wide significance has now been shown for SNPs in different non-HLA MS risk genes. Several of these risk genes, including CD58 and CLEC16A, are shared by different autoimmune diseases. Fine mapping studies will be needed to determine the functional contributions to distinct autoimmune phenotypes.